LO44: Simulation in the continuing professional development of Canadian academic emergency physicians: a national survey. (May 2019) - Forristal, C.; Russell, E.; McColl, T.; Petrosoniak, A.; Mastoras, G.; Caners, K.; Thoma, B.; Szulewski, A.; Huffman, J.; Dakin, C.; Chaplin, T.; Woolfrey, K.; et al.
Abstract : Introduction : Capitalizing on the success of Simulation-Based Education (SBE) in residency-training programs, simulation has been gradually integrated into Continued Professional Development (CPD) programs for Emergency Physicians (EPs) in Canada. This study sought to characterize how Canadian academic emergency medicine (EM) departments have implemented SBE for CPD.Methods : We conducted two national surveys: 1) the National Faculty Simulation Status Assessment Survey, administered by telephone to the simulation directors (or equivalent) at 20 Canadian academic EM sites and 2) the Faculty Simulation Needs Assessment Survey administered online to all full-time EPs across 9 Canadian academic EM sites.Results : The response rates for the National Status and Needs Assessment Surveys were 100% (20/20), and 40% (252/635), respectively. The majority (60%) of Canadian academic EM sites reported utilizing SBE for CPD, though only 30% reported dedicated funding support. EPs reported participating in a median of 3 hours per year of SBE (IQR 1-6 hours). Reported incentivization offered in the form of continued medical education credits varied between simulation directors (67%) and EPs (44%). Simulation directors identified several significant barriers to SBE including a lack of faculty time, fear of peer judgment, and faculty inexperience. In contrast, EP-identified barriers included time commitments outside of shift, lack of opportunities, and lack of departmental. The three most common topics of interest for SBE by EPs were performance of rare procedures, pediatric resuscitation, and neonatal resuscitation. Interprofessional involvement in SBE CPD was valued by both simulation directors and EPs, with most EPs (79%) indicating it is useful.Conclusion : Most Canadian EPs and simulation directors recognize the value of SBE for CPD, yet it is only utilized, infrequently, by 67% of Canadian academic EM departments for this purpose. This may be explained, in part, by poor incentivization for participation. Simulation directors and EPs noted different barriers to SBE implementation for CPD suggesting the need for dialogue to improve utilization. As SBE for CPD is incorporated more frequently, and at more sites, content should be guided by local needs assessments with an emphasis on interprofessional participation.